High final energy of gallium arsenide laser increases MyoD gene expression during the intermediate phase of muscle regeneration after cryoinjury in rats - Santos, Caroline Pereira; Aguiar, Andreo Fernando; Giometti, Ines Cristina; Mariano, Thaoan Bruno; de Freitas, Carlos Eduardo Assumpção; Nai, Gisele Alborghetti; de Freitas, Selma Zambelli; Pai-Silva, Maeli Dal [UNESP]; Pacagnelli, Francis Lopes (Springer Nature, 2018)
The aim of this study was to determine the effects of gallium arsenide (GaAs) laser on IGF-I, MyoD, MAFbx, and TNF-α gene expression during the intermediate phase of muscle regeneration after cryoinjury 21 Wistar rats were divided into three groups (n = 7 per group): untreated with no injury (control group), cryoinjury without GaAs (injured group), and cryoinjury with GaAs (GaAs-injured group). The cryoinjury was induced in the central region of the tibialis anterior muscle (TA). The region injured was irradiated once a day during 14 days using GaAs laser (904 nm; spot size 0.035 cm2, output power 50 mW; energy density 69 J cm−2; exposure time 4 s per point; final energy 4.8 J). Twenty-four hours after the last application, the right and left TA muscles were collected for histological (collagen content) and molecular (gene expression of IGF-I, MyoD, MAFbx, and TNF-α) analyses, respectively. Data were analyzed using one-way ANOVA at P < 0.05. There were no significant (P > 0.05) differences in collagen density and IGF-I gene expression in all experimental groups. There were similar (P < 0.05) decreases in MAFbx and TNF-α gene expression in the injured and GaAs-injured groups, compared to control group. The MyoD gene expression increased (P = 0.008) in the GaAs-injured group, but not in the injured group (P = 0.338), compared to control group. GaAs laser therapy had a positive effect on MyoD gene expression, but not IGF-I, MAFbx, and TNF-α, during intermediary phases (14 days post-injury) of muscle repair.
Keywords: Gallium arsenide laser; IGF-I; MAFbx; Muscle regeneration; MyoD; TNF-α gene expression